2018
DOI: 10.1111/1745-9125.12195
|View full text |Cite
|
Sign up to set email alerts
|

Putting homicide followed by suicide in context: Do macro‐environmental characteristics impact the odds of committing suicide after homicide?*

Abstract: Homicide followed by suicide remains an understudied phenomenon in the criminological literature. This is due, in part, to methodological and statistical limitations—much of the extant research includes small samples and has not kept pace with quantitative advances. Moreover, scholarship on homicide–suicide has been focused almost exclusively on individual risk factors, discounting contextual influences. In this study, we examine whether macro‐environmental characteristics affect the odds of suicide after a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 128 publications
1
24
0
Order By: Relevance
“…Almost as notable was the inability of contextual gun availability to distinguish homicide-suicide from homicide-only and suicide-only at the individual-level. Although some may take this as evidence that the etiology of homicide-suicide does not diverge from its component acts at the macro-level, we note that concentrated disadvantage reduced the odds of suicide following homicide after controlling for incident-level characteristics, consistent with prior work (Fridel & Zimmerman, 2019b). Relatedly, and as noted above, much of the empirical work on homicide-suicide has focused on examining whether homicide-suicide is primarily suicide-driven, primarily homicide-driven, or a different form of violence entirely (Eliason, 2009; Liem & Nieuwbeertaa, 2010; Logan et al, 2008).…”
Section: Resultssupporting
confidence: 87%
“…Almost as notable was the inability of contextual gun availability to distinguish homicide-suicide from homicide-only and suicide-only at the individual-level. Although some may take this as evidence that the etiology of homicide-suicide does not diverge from its component acts at the macro-level, we note that concentrated disadvantage reduced the odds of suicide following homicide after controlling for incident-level characteristics, consistent with prior work (Fridel & Zimmerman, 2019b). Relatedly, and as noted above, much of the empirical work on homicide-suicide has focused on examining whether homicide-suicide is primarily suicide-driven, primarily homicide-driven, or a different form of violence entirely (Eliason, 2009; Liem & Nieuwbeertaa, 2010; Logan et al, 2008).…”
Section: Resultssupporting
confidence: 87%
“…Accordingly, Stack (1997) found that killing a former spouse, child, spouse, and friend increased the odds of subsequent suicide by approximately 13, 10, 8, and 2 times, respectively, concluding that the etiology of homicide-suicide lies in an “intimate” and “long-term” personal relationship. Similarly, Fridel and Zimmerman (2019) found that the odds of suicide following homicide were highest for offenders who killed their children, followed by offenders who killed a spouse, parent, and friend. This diverges from the victim-offender relationship in homicide-only incidents, in which offenders tend to target friends, acquaintances, and strangers (Daly and Wilson 1988; Decker 1993).…”
Section: Conceptual Backgroundmentioning
confidence: 96%
“…Homicide-suicide is rooted in a close victim-offender relationship. As few as 2 percent of homicide-suicide perpetrators victimize persons unknown to them (Fridel and Zimmerman 2019), and the overwhelming number of homicide-suicides involve family members and intimate partners. Accordingly, Stack (1997) found that killing a former spouse, child, spouse, and friend increased the odds of subsequent suicide by approximately 13, 10, 8, and 2 times, respectively, concluding that the etiology of homicide-suicide lies in an “intimate” and “long-term” personal relationship.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 2 more Smart Citations